Rehabilitation of failing dentition with interim immediate denture prosthesis - Amit Sharma; Divia Chugh; Bhavika Sachdeva; Manish Sen Kinra (Wolters Kluwer Medknow Publications, 2016)
Advances in therapy have helped patients with periodontal disease to retain part of their natural dentition for an extended period. These patients can be well served by properly designed removable partial dentures. For the patient facing the loss of all his/her remaining natural teeth, there are three treatment options. One is for the patient to have all remaining teeth extracted and wait for 6-8 weeks for the extraction sites to heal. The conventional complete denture is made following healing, leaving the patient without teeth not only during the healing phase but also during the time required for the fabrication of the conventional complete denture. A second option is to convert an existing removable partial denture into an interim immediate complete denture. A third option is to make a conventional immediate complete denture. The aim of this clinical report was to describe the fabrication of interim immediate denture in a patient with hopeless existing dentition.